ANALYSIS OF VALIDITY AND RELIABILITY IN STUDENT COLLABORATION SKILLS RESEARCH ON FIQH SUBJECTS AT MAN 1 PEKANBARU - Vina Novita; Nurul Habibah Arfizeah; Risnawati; Miftahir Rizqa (STKIP Subang, 2025)
This study aims to analyze the validity and reliability of the questionnaire instrument developed to measure students' collaboration skills in Islamic Religious Education (PAI) subjects, especially in Fiqh learning. Collaboration skills are one of the key competencies of 21st century education, so valid and reliable instruments are indispensable to produce accurate and accountable measurements. This study used a quantitative survey method involving 20 grade 10 students of MAN 1 Pekanbaru City who were selected through random sampling techniques. Data analysis was carried out through a validity test using Corrected Item-Total Correlation and a reliability test using Cronbach's Alpha. The results showed that 8 out of 11 statements were declared valid because they had a correlation value higher than the r table (0.443). Meanwhile, the reliability test yielded a Cronbach's Alpha value of 0.777 which is in the acceptable category. Thus, the instrument is declared valid and reliable so that it is suitable to be used to measure students' collaboration skills in Fiqh learning. This study provides empirical evidence on the psychometric quality of collaborative skill assessment instruments in the context of PAI education.